Can the vaccinations end the Covid-19 pandemic? - Alfred Greiner; Benjamin Darkwa Owusu (Bielefeld University, Faculty of Business Administration and Economics, 2022)
In this paper we empirically analyze the effect of the vaccinations against the SARS-CoV-2 virus on the Covid-19 pandemic for European countries from February 2021 to February 2022 with weekly data. We perform panel fixed effects estimations, GMM estimations and nonlinear penalized spline estimations. We find a statistically significant and positive relation between the share of infections with the SARS-CoV-2 virus and the share of vaccinated people. That holds for both fully vaccinated persons and for people having received a booster injection as well. As regards hospitalizations we find weak empirical evidence for a negative relation between vaccinations and the rate of hospitalizations.
urn:nbn:de:0070-pub-29616726
Keywords: C10; D62; I10; 610; Covid-19; vaccination; pandemic; externalities